Regulatory Pathways for Smart Grid Development in China - Gert Brunekreeft; Till Luhmann; Tobias Menz; Sven-Uwe Müller; Paul Recknagel (Springer Open, 2015)
The study's recommendations describe institutional elements in the context of electric power sector regulation and has the objective to increase the understanding of the interdependencies of the institutional elements. In future work, the study results might be employed for designing very specific regulatory policies. The recommendations developed in this study focus primarily on the regulatory framework for smart grids and contains a quite detailed description of how the German electricity markets evolved. It also focuses on the effects of ambitiously expanding generation capacities of renewable energy sources (RES) on established electricity markets. The presented evidence will provide insights on how the regulatory framework in China could be designed to foster smart grids developments in the context of establishing electricity markets and expanding RES generation capacities.
Keywords: 620; Energy Policy; Economics and Management; Energy Technology; Environmental Law/Policy/Ecojustice